2002
DOI: 10.1037/0022-0663.94.2.396
|View full text |Cite
|
Sign up to set email alerts
|

Making the grade but feeling distressed: Gender differences in academic performance and internal distress.

Abstract: There is disagreement over whether girls or boys are at risk in the context of school. Girls outperform boys in school, particularly in stereotypically feminine subjects. However, girls are also more vulnerable to internal distress than boys are. The aim of this research was to understand this pattern of gender differences. Gender differences in academic performance and internal distress were examined in elementary school children moving into adolescence. Girls outperformed boys across all 4 subjects but were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
253
2
13

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 369 publications
(310 citation statements)
references
References 41 publications
39
253
2
13
Order By: Relevance
“…The analyses confirmed a gender gap in academic achievement (Pomerantz, Altermatt, & Saxon, 2002;Statistics Norway, 2013a) in our North Norwegian sample. Female students had a higher GPA than male students.…”
Section: Demographic Factorssupporting
confidence: 68%
“…The analyses confirmed a gender gap in academic achievement (Pomerantz, Altermatt, & Saxon, 2002;Statistics Norway, 2013a) in our North Norwegian sample. Female students had a higher GPA than male students.…”
Section: Demographic Factorssupporting
confidence: 68%
“…Previous work has shown that girls may receive better grades than boys but at the same time may be more vulnerable to internal distress (e.g., Pomerantz et al, 2002). Notably, the same factors may contribute to both enhanced grades and heightened internal distress for girls.…”
Section: Discussionmentioning
confidence: 95%
“…tions to the contrary, girls also receive equal or higher grades than do boys in stereotypically masculine subject areas, such as math and science (e.g., American College Testing Program, 1997;Jacobs, 1991;Pomerantz et al, 2002; for reviews, see American Association of University Women, 1999;Dwyer & Johnson, 1997;Kimball, 1989). Hence, in terms of grades, girls outperform boys in both stereotypically feminine and masculine areas.…”
mentioning
confidence: 99%
“…In many countries, it is true throughout primary, secondary school, and even in college years (e.g., Epstein, Elwood, Jey, & Maw, 1998;Mau & Lynn, 2001;Perkins, Kleiner, Roey, & Brown, 2004;Pomerantz, Alterman, & Saxon, 2002;Van Houtte, 2004;Willingham & Cole, 1997;Wong, Lam, & Ho, 2002). Although women are still underrepresented in science and mathematics (Ceci, Williams, & Barnett, 2009), they compose nearly 60% of the university student populations in many developed countries (Johnson, 2008).…”
Section: Introductionmentioning
confidence: 99%